Human and Economic Resources Mapping Analysis to Evaluate the SDGs Accomplishment in South Kalimantan, Indonesia - Ratih Fitria Putri; Josaphat Tetuko SriSumantyo; Sukamdi Sukamdi; Rika Harini (Faculty of Geography, Universitas Gadjah Mada, 2019)
Natural resource abundance in South Kalimantan has been expected to optimize public services. The SDGs accomplishment requires an equitable implementation in economic, social, and environmental aspects. This research aimed to (1) discover the human and economic condition and (2) determine the development direction of South Kalimantan Province. It was based on institutional-secondary data that were processed in GIS software and analyzed with both qualitative and quantitative approaches. The results showed that: (1) the human resources in South Kalimantan could accelerate regional development—however, some of the qualitative indicators are associated with poverty complicated by gender disparity—, while the land resources became increasingly limited due to intensive agricultural practices that caused the rise of industrial and trade sectors; and (2) the development of South Kalimantan should improve people’s perception of gender-related topics, recruit more medical workers, and reduce pressures on agricultural land by switching into stable industrial activities.